If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x+1/2x+(-1/2)=-(1/2)
We move all terms to the left:
6x+1/2x+(-1/2)-(-(1/2))=0
Domain of the equation: 2x!=0We add all the numbers together, and all the variables
x!=0/2
x!=0
x∈R
6x+1/2x+(-1/2)-(-(+1/2))=0
We get rid of parentheses
6x+1/2x-1/2-(-(+1/2))=0
We calculate fractions
6x+()/16x^2+(-(-(+1*2x)/16x^2=0
We multiply all the terms by the denominator
6x*16x^2+(-(-(+1*2x)+()=0
We calculate terms in parentheses: +(-(-(+1*2x)+(), so:Wy multiply elements
-(-(+1*2x)+(
96x^3+(-(-(+1*2x)+()=0
We calculate terms in parentheses: +(-(-(+1*2x)+(), so:We do not support expression: x^3
-(-(+1*2x)+(
| 20+16p=81 | | 12x-34=8x+15 | | -5=n/3 | | (3x+8)2^=64 | | 2x+9+3x+3x=3x+1 | | 2x+9+3x+3x=2x+8 | | 2x+9+3x+3x=2x+7 | | 2x+9+3x+3x=2x+6 | | 2x+9+3x+3x=2x+5 | | 2x+9+3x+3x=2x+4 | | 2x+9+3x+3x=2x+3 | | 2x+9+3x+3x=2x+2 | | 2x+9+3x+3x=2x+1 | | 2x+9+3x+3x=1x+9 | | 2x+9+3x+3x=1x+8 | | 2x+9+3x+3x=1x+7 | | 2x+9+3x+3x=1x+6 | | 2x+9+3x+3x=1x+5 | | 2x+9+3x+3x=1x+3 | | 2x+9+3x+3x=1x+2 | | 2x+9+3x+3x=1x+1 | | 2x+9+3x+3x=1x+4 | | 5y+11=30 | | 2x+9+3x+3x=2x+9 | | x/2+x/2+x/2+(-18)=10x-1 | | -13-(-27)=x/11 | | 0.15-t×100=0.02 | | y^2+2y+1+3y(6y+1)=19y^2 | | 8r-6r=10 | | 29(x-5)=90 | | 2x^-9x=x^-20 | | 5p–98=2p–20 |